Use of fish-farming wastewater in lettuce cultivation - Guimaraes, Isaias P.; Oliveira, Francisco de A. de; Torres, Salvador B.; Pereira, Francisco E. C. B. [UNESP]; Franca, Francisco D. de; Oliveira, Mychelle K. T. de (Univ Federal Campina Grande, 2016)
Lettuce stands out as the main leafy vegetable consumed in Brazil, with divergence regarding adaptability to different environmental conditions, which include salinity. The objective of the work was to evaluate the response of lettuce cultivars to the use of saline wastewater from fish farming. The experiment was conducted in a completely randomized design with four replicates, in a factorial 7 x 4, corresponding to seven cultivars (Regiane, Vera, Isabela, Elisa, Amelia, Lavinia and Angelina) and four salt concentrations (1.2, 2.2, 3.2 and 4.2 dS m(-1)). The evaluated characteristics were: number of leaves, leaf area, crown diameter and shoot fresh and dry matter. Diluted wastewater from fish farming can be used in the preparation of solution for fertigation of lettuce. The cultivars Regiane and Elisa had higher production of leaves and leaf area, while Amelia and Angelina were the most productive in terms of biomass. The cultivars Vera, Isabela, Amelia and Angelina were more tolerant to the salinity of the fertigation solution.
Keywords: Lactuca sativa; water resources; salinity; sustainability